Sharma : un entrepôt de commerce médiéval sur La Côte du Hadramawt : (Yémen, ca 980-1180) - Bernard, V. (British Foundation for the Study of Arabia monographs, 2015)
Cited by al-Muqaddasi in c.985 and then by al-Idrisi in c.1150, the medieval port of Sharma was discovered in 1996 at the extremity of the Ra's Sharma, 50km east of al-Shihr on the Hadramawt coast of Yemen; it was excavated in 2001-2005. This unique site was actually a transit entrepôt, a cluster of warehouses probably founded by Iranian merchants and entirely devoted to the maritime trade. It knew a rather short period of activity, between around 980 and the second half of the 12th century, which may be acknowledged as the Sharma horizon. Excavations proved that this settlement experienced six occupation phases, which are closely related to the political and economic developments in the region at that time.